REFLEKSI KONTROVERSI PADA MASYARAKAT DEMOKRATIF DALAM MEDIA TWITTER (Studi Fenomenologi Tentang Pengalaman Followers Akun Twitter @farhatabbaslaw Dalam Memandang Kepemimpinan Joko Widodo) - Allice Chitra Yapardi; Anastasia Monica Tjahyadi; Herlika Fransisca Wijaya; Nur Desilawati (Universitas Bunda Mulia, 2013)
Twitter is a social media based from text, with some of “kicauan” consists of 140 characters for a content. Twitter used as a medium to knows or gives an informations to all Twitter members. Twitter is a forum for their members to gives their opinions about any themes, including politics, law, culture and social problem. One of many famous twitter members, who actived to give his opinions and expressions his things about their politicsidea is @Farhatabaslaw. Farhat Abbas, as a political and as a candidate of Indonesian president who have that twitter account. He always gives an opinion about the goverment of Jakarta’s governer, Joko Widodo and Basuki Tjahaja Purnama. The followers of @Farhatabaslaw gives their opinions. The followers of Farhat Abas’s Tweet give pro and contra opinions.In this research, the pro and contra opinion says they have an experience about they participate to gives their opinion, consists of give a support to Farhat Abas’s opinion, underestimate the opinions from Farhat Abas, and give a neutral opinions. The follower’s motive about their participate because they wan’t to know about Farhat Abas who a phenomenal figure, they wan’t to expression their opinions, and they want to answercuriosity of the tweet from @farhatabaslaw.Keywords: Social Media, Followers @farhatabbaslaw, Phenomenology, Controversy